2009
DOI: 10.1007/s00726-009-0393-x
|View full text |Cite
|
Sign up to set email alerts
|

Restriction factors of retroviral replication: the example of Tripartite Motif (TRIM) protein 5α and 22

Abstract: Viral tropism, replication, and pathogenesis are determined by multiple interactions between the pathogen and the host. In the case of retroviruses, and in particular, the human immunodeficiency virus, the specific interaction of the envelope protein with the host receptors and co-receptors is essential to gain entry in the cells. After entry, the success of retroviruses to complete their life cycle depends on a complex interplay between the virus and host proteins. Indeed, the cell environment is endowed with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 95 publications
0
12
0
Order By: Relevance
“…In this regard, early reports suggested that endogenously produced IFN-␣ contributes to restricted HIV-1 viral replication in U937 promonocytic cells (40), while it was later suggested to interfere with HIV-1 long-terminal-repeat (LTR)-driven transcription (25). Among other IFN-induced genes, TRIM22, also known as Staf50 (33,70), was originally identified in a screening for IFN-inducible genes in the human B lymphoblastoid Daudi cell line and was reported to inhibit HIV replication at transcriptional, posttranscriptional, or posttranslational levels following transfection in different target cells (3,70).…”
Section: Trim22 Knockdown (Kd) Rescued Hiv-1 Long-terminal-repeat (Ltmentioning
confidence: 99%
“…In this regard, early reports suggested that endogenously produced IFN-␣ contributes to restricted HIV-1 viral replication in U937 promonocytic cells (40), while it was later suggested to interfere with HIV-1 long-terminal-repeat (LTR)-driven transcription (25). Among other IFN-induced genes, TRIM22, also known as Staf50 (33,70), was originally identified in a screening for IFN-inducible genes in the human B lymphoblastoid Daudi cell line and was reported to inhibit HIV replication at transcriptional, posttranscriptional, or posttranslational levels following transfection in different target cells (3,70).…”
Section: Trim22 Knockdown (Kd) Rescued Hiv-1 Long-terminal-repeat (Ltmentioning
confidence: 99%
“…[18][19][20][21][22][23][24][25][26] For example, TRIM5α exhibits strong activity against the human immunodeficiency virus presumably by targeting the integrating complex for degradation. 21,[27][28][29] The following indirect evidence suggest that MID1 functions as a Ub ligase to target the catalytic subunit of protein phosphatase 2A (PP2Ac) for ubiquitination: (i) an increased accumulation of polyubiquitinated PP2Ac was observed in normal human embryonic fibroblasts but not in XLOSderived embryonic fibroblasts when the cells were consists of seven domains whose order is conserved. The RING and Bbox domains are Cys-rich and His-rich zinc-binding domains that adopt ββα RING folds commonly observed for Ub E3 ligases.…”
Section: Introductionmentioning
confidence: 99%
“…treated with proteosome inhibitors (ii) ubiquitination of PP2Ac in XLOS-derived fibroblasts can be rescued with the expression of wild-type MID1; and (iii) PP2Ac and phosphoproteins accumulate in XLOS-derived fibroblasts in which MID1 is mutated. 6,7,10,21,30 Ubiquitination of PP2Ac requires MID1 to first bind alpha4, a novel regulatory subunit of PP2Ac. [6][7][8]10,31 In studies with COS-7 cells, increased alpha4 expression resulted in a redistribution of MID1 from the microtubule to the cytoplasm, suggesting that the MID1-alpha4 complex increases the dephosphorylation of MID1 by PP2Ac.…”
Section: Introductionmentioning
confidence: 99%
“…Because the common ancestor of Old World monkeys and apes existed around 25 million years ago, the divergence of these host proteins may pose an obstacle to cross-species infection. In addition, primates (including humans) encode a number of host restriction factors, which have evolved as part of their innate immune response to protect against infection with a wide variety of viral pathogens (Malim and Emerman 2008;Neil and Bieniasz 2009;Kajaste-Rudnitski et al 2010). Although viruses have, in turn, found ways to antagonize these restriction factors,…”
Section: Host-specific Adaptationsmentioning
confidence: 99%